Value Engineering Construction Of The Unisa Campus Saintek Building 2 - Ramadhana Sangyang Ady; Fredy Kurniawan; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2021)
This Value Engineering analysis is carried out to analyze or organize a construction of the SAINTEK UINSA 2 building which aims to produce appropriate quality that does not change the function and also there are no unnecessary costs considering that the construction of this building has a building area of ??40 x 19 = 760 m2 which cost Rp. 37,108.056,260.81. In this analysis, an analysis is carried out or to identify the function of a product or service that aims to fulfill the required function at the lowest price by providing an alternative from the creative ideas obtained to give to the owner so that there is no need for an increase in costs. From the VE analysis on the construction of the SAINTEK UINSA 2 building, the total initial cost savings on the slab work were initially Rp. 624,429,524.15 and after applying Value Engineering analysis using alternative 2, the cost is Rp. 527,876,352.19 which is more economical worth Rp. 96,553,171.96 or 15.46% of the initial price. On the 1st floor work (1st floor ) EL. -0.05 in which there is a formwork slab which is considered to have a high cost, which initially used nails and wooden blocks, which was changed to 50.50 hollow iron and bendrat wire.